Sexuality post gynaecological cancer treatment: a qualitative study with South African women. Issue 9 (23rd September 2020) - Pitcher, Sorrel; Fakie, Nazia; Adams, Tracey; Denny, Lynette; Moodley, Jennifer
Abstract : Objectives: This study investigated women's experiences of their sexuality post gynaecological cancer treatment. Using a holistic sexuality framework, the study explored how women felt their sexual functioning, sexual relationships and sexual identity had been affected by treatment. Design: The study was qualitative in nature and made use of an interpretive descriptive design. Data were analysed using thematic analysis. Setting: Data collection took place at a follow-up clinic within the gynaeoncology unit at a public-sector tertiary hospital in Cape Town, South Africa. Participants: Purposive sampling was used to recruit participants, and the final sample consisted of 34 women aged 29–70 (x ´ =52). All women had received a gynaecological cancer diagnosis and had been treated with either surgery, chemotherapy, radiation or a combination of these. On average, the participants were between 12 and 30 months post treatment. Results: Women expressed how their sexual functioning post treatment was both nuanced and complex, how heteronormative gender expectations influenced their intimate relationships, and how they experienced a re-embodiment of their sexual subjectivity post treatment. Participants felt that more sexual functioning information from healthcare providers, as well as peer support groups, would assist them in navigating the sexuality changes they experienced. Conclusions: The findings of this study broaden conceptualisations of sexuality post treatment by detailing the ways that it is complex, nuanced, relational and ever shifting. More research is needed about how to incorporate holistic psychosexual support post treatment into the public healthcare system in South Africa.